2020
DOI: 10.1364/josab.401157
|View full text |Cite
|
Sign up to set email alerts
|

Counter-propagating spectrally uncorrelated biphotons at 1550  nm generated from periodically poled MTiOXO4 (M = K, Rb, Cs; X = P, As)

Abstract: We theoretically investigated spectrally uncorrelated biphotons generated in a counter-propagating spontaneous parametric downconversion (CP-SPDC) from periodically poled M T i O X O 4 ( M = K , Rb, Cs; X = P , As) crystals. By numerical calculation, it was found that the five crystals from the KTP family can be used to generate heralded single photons with high spectral purity and wide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We can see that in the traditional co-propagating process the coefficients of frequency offsets only depend on the difference of the reciprocal of group velocities, and thus in such process the phase-matching function is usually engineered by selecting working frequencies and structures to control the dispersion and group velocities [34]. While, in the counter-propagating process, the coefficients also depend on the sum of the group velocities, enabling intrinsic features for phase-matching engineering [20][21][22][23][24][25][26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can see that in the traditional co-propagating process the coefficients of frequency offsets only depend on the difference of the reciprocal of group velocities, and thus in such process the phase-matching function is usually engineered by selecting working frequencies and structures to control the dispersion and group velocities [34]. While, in the counter-propagating process, the coefficients also depend on the sum of the group velocities, enabling intrinsic features for phase-matching engineering [20][21][22][23][24][25][26].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, counter-propagating quasi-phase-matching (QPM) spontaneous parametric down-conversion (SPDC) process has been extensively studied due to its unique spectral properties [19,20], such as narrow bandwidth [21,22] and frequency uncorrelated [23][24][25][26] photon pairs. In contrast to the traditional co-propagating process, in the counter-propagating process the phase-matching function is greatly affected by the counter propagation of the signal and idler photons, and hence such method can be applied in a large range of nonlinear materials and working wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…The momentum mismatches can be perfectly compensated through the periodic poling method. [36,37] By periodically modifying the susceptibility of NPC in real space, we can obtain six peak values in its Fourier space (reciprocal space) to perform QPM. The designed distribution of NPC's χ (2) is shown in Fig.…”
Section: Overall Hyperentanglement Schemementioning
confidence: 99%
“…Therefore, a nonlinear interferometer (NLI) can be used to engineer quantum state. N-stage NLI, consisting of N-stage nonlinear gain medium with one piece dispersion modulation medium between every adjacent two, has applications in dispersion compensation of optical parametric amplifier, [13][14][15][16] precision phase measurement beyond standard quantum limit, [17][18][19] super-resolution spectroscopy and imaging [20,21] and biphoton spectrum shaping. [22] Cui et al [23][24][25] have demonstrated that the spectrally uncorrelated biphotons can be obtained via fiber NLI, therein dispersion-shifted fiber as nonlinear gain medium and single mode fiber as dispersion modulation medium in a small frequency detuning case.…”
Section: Introductionmentioning
confidence: 99%